Microinjection of smg/rap1/Krev-1 p21 into Swiss 3T3 cells induces DNA synthesis and morphological changes. - Yoshida, Y (1992)
Microinjection of either Ki-rasVal-12 p21 or the GDP-bound form of Ki-ras p21 plus smg GDP dissociation stimulator (GDS), a stimulatory GDP/GTP exchange protein for Ki-ras p21, smg/rap1/Krev-1 p21, and rho p21, into quiescent Swiss 3T3 cells induced DNA synthesis irrespective of the presence or absence of insulin. The guanosine 5'-(3-O-thio)triphosphate (GTP gamma S)-bound form of smg p21B or the GDP-bound form of smg p21B plus smg GDS also induced DNA synthesis but only in the presence of insulin. Either the GDP-bound form of Ki-ras p21 or the same form of smg p21B alone was inactive, but smg GDS alone was slightly active only in the presence of insulin. The morphology of the cells was analyzed by scanning electron, phase-contrast, and confocal laser scanning microscopies. Ki-rasVal-12 p21 induced membrane ruffling irrespective of the presence or absence of insulin. The GTP gamma S-bound form of smg p21B showed the same effect only in the presence of insulin. Either the GDP-bound form of Ki-ras p21, the same form of smg p21B, or smg GDS alone was inactive. Upon microinjection of Ki-rasVal-12 p21, stress fibers markedly decreased and the cells became round and piled up. In contrast, upon microinjection of the GTP gamma S-bound form of smg p21B, stress fibers did not markedly decrease and the cells neither became round nor piled up. These results indicate that both ras p21 and smg p21 are mitogenic in Swiss 3T3 cells but that their actions are slightly different.